The Effectiveness of a Cognitive Rehabilitation Program on the Cognitive Performance of Elementary School Students with Mathematical Learning Disabilities - Moradi, Majid (Mental Health and Lifestyle Journal, 2024)
The present study aimed to investigate the effectiveness of a cognitive rehabilitation program on the cognitive performance of elementary school students in the second cycle who have been diagnosed with mathematical learning disabilities. This study was applied in purpose and used a quasi-experimental method with a pretest-posttest control group design. The sampling method was convenience sampling. In this process, the researcher referred to the Hafez Educational and Rehabilitation Center for Special Learning Disorders in Shiraz and identified second-cycle elementary students who had been diagnosed with mathematical learning disabilities based on diagnostic interviews and existing documentation in their clinical files. Based on the diagnoses made by specialists at the counseling center, a total of 30 students who met the inclusion criteria were selected to participate in the study. Data collection was conducted using the Cognitive Abilities Questionnaire developed by Nejati (2013). Data analysis was performed using SPSS software through both descriptive and inferential statistics. The findings demonstrated that the cognitive rehabilitation program had a statistically significant impact on the cognitive performance of elementary students with mathematical learning disabilities.